The Relationship Between Medical Records Employee Performance And Patient Satisfaction - Andrias Feri Sumadi; Ery Rustiyanto; Agung Dwi Saputro; Dewi Cahyaningrum (Indonesian Health Issue, 2026)
Background: The best patient care in healthcare facilities is essential to achieve patient satisfaction. Objective: To determine the relationship between medical records staff performance and patient satisfaction in the Outpatient Admissions Area (TPPRJ) in an effort to improve the quality of healthcare services at Nur Hidayah Hospital, Bantul. Method: This study used a quantitative, cross-sectional, observational approach, involving 93 patient respondents selected via simple random sampling. Data were collected through observation and questionnaires using five dimensions of medical records staff performance: reliability, responsiveness, assurance, tangibles, empathy, and patient satisfaction. Results: The study shows the percentage of scores for each assessment dimension. The highest percentage was for patients who were satisfied with the staff's performance (64 respondents (68.8%), followed by patients who were very satisfied with the staff's performance (23 respondents (24.7%), then the category of patients who were only quite satisfied with the staff's performance (6 respondents (6.5%), and the lowest was for those who were dissatisfied and very dissatisfied with the staff's performance (0 respondents (0%). Based on the results of the analysis using the chi-square test conducted on patient satisfaction with employee performance, the p-value obtained was 0.001 (p <0.05), so Ho in the study was rejected, and H1 was accepted, which means there is a relationship between patient satisfaction and the performance of TPPRJ employees at Nur Hidayah Hospital, Bantul. Conclusion: Improving the quality of service must be done comprehensively, covering all aspects of service, facilities, and communication.